Adaptation of persons with disabilities to inclusive education in the university as a condition of their successful functioning in the labour market - E. V. Gurova; N. I. Laas; A. V. Pritolyuk; I. A. Romanova (Вестник университета, 2019)
The main way to implement this principle of equality in the education of persons with disabilities and persons with disabilities (HIA) is now inclusive education at all levels of education throughout life. The basic concepts related to disability, integration of persons with disabilities into society, educational environment have been highlighted in the article, the differences in the understanding and interpretation of these concepts have been shown. The factors of adaptation of students with invalidity and disabilities have been disclosed. The formation of an inclusive educational environment in the University is impossible without improving the management of inclusive education in higher education system.